IMPLEMENTASI KEBIJAKAN PROGRAM USAHA EKONOMI PRODUKTIF MELALUI KUBE DI DESA CITARIK PALABUHANRATU SUKABUMI - Purwanti Basuki (STISIP Widyapuri Mandiri, 2022)
Productive Economic Enterprises Program (UEP) is one approach to social welfare programs to accelerate poverty eradication. Through UEP the poor get facilities to be used in business through the Joint Business Group (KUBE). This study uses a qualitative approach with a descriptive method. This research is intended to obtain information about the implementation of the Productive Economic Enterprises (UEP) program through KUBE using the implementation model of George C. Edward III. The results of the analysis concluded that (1) the implementation of the Productive Economic Enterprises (UEP) policy through KUBE in Citarik Village, Palabuhanratu District did not go well, (2) there were several obstacles in the implementation of the Productive Economic Enterprises (UEP) policy through KUBE in Citarik Village. Palabuhanratu District, and (3) several efforts have been made to overcome the obstacles that occur.